2019
DOI: 10.4236/as.2019.106058
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Development of Bell Peppers Submitted to Fertilization with Biochar and Nitrogen

Abstract: The experiment was carried out in the greenhouse of the DEAg/UFCG, Campina Grande (PB), Brazil, to evaluate the growth and development of the bell pepper subjected to fertilization with biochar and nitrogen. The experiment was conducted in pots under greenhouse conditions. Treatments were arranged in a completely randomized design, in 4 × 4 factorial scheme, relative to four doses of biochar (0; 7; 14 and 21 m 3 •ha −1) and four doses of nitrogen (0; 40; 80 and 120 kg•ha −1), with three replicates. Considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Its nutritional characteristics vary depending on the material used in pyrolysis, but there is usually an increase in the capacity for cation exchange, macronutrients, micronutrients and pH [4] [5]. According to some authors Faria et al [6] and Lima et al [7], the use of biochar in agriculture promotes an increase in crop productivity due to the greater absorption of nutrients by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Its nutritional characteristics vary depending on the material used in pyrolysis, but there is usually an increase in the capacity for cation exchange, macronutrients, micronutrients and pH [4] [5]. According to some authors Faria et al [6] and Lima et al [7], the use of biochar in agriculture promotes an increase in crop productivity due to the greater absorption of nutrients by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Ớt chuông (Capsicum annuum) là một loại cây thực phẩm thuộc họ Solanaceae, là một trong những cây được trồng phổ biến ở Brazil [8]. Quả ớt chuông có nhiều màu sắc khác nhau với hương vị ít cay nên được xếp vào loại ớt ngọt chứa rất nhiều hàm lượng vitamin A, C và một số chất chất thiết yếu khác [9]. Trong canh tác, có rất nhiều yếu tố ảnh hưởng đến cây trồng.…”
Section: Giới Thiệuunclassified
“…The biochar obtained at 450 • C from pistachio improved soil drainage and plant availability. Also, a greenhouse study carried out by Jabborova et al [18] showed that the addition of 2 and 3% of commercial biochar to the soil improved the lettuce yield, while Faria et al [19] and De Lima et al [20] found that the biochar obtained from poultry litter amendments promoted increased cultivation productivity. Sánchez et al [21] added to soil 5, 10, and 15% of almond biochar and found that the lowest ratio of biochar presented better results in arugula seedlings.…”
Section: Introductionmentioning
confidence: 99%